Intergroup behavior in organizations a field test of social identity theory - Hennessy, Josephine; West, Michael A. (Sage Publications Inc., 1999)
This study tests social identity theory and realistic conflict theory by examining intro-and intergroup relations in a team-based community-health care organization. The relationships between people's patterns of identification (with their work and with the organization) and their perceptions of intergroup competition for source resources are related to in-group favoritism. Questionnaire data gathered from 112 participants, who were members of 17 work groups within the organization, reveal that strong identification with the work group rather than the organization is related to high levels of in-group favoritism, thus supporting the relevance of social identity theory in an organizational setting. In-group identification did not predict between-group discrimination in resource distribution, although such discrimination was demonstrated. We suggest that in applied settings the factors influencing social behavior are more complex than in laboratory studies but that social identity theory has clear practical importance for understanding and influencing the effectiveness of team-based organizations.